2018
DOI: 10.1007/s00424-018-2204-2
|View full text |Cite
|
Sign up to set email alerts
|

NAD metabolism and the SLC34 family: evidence for a liver-kidney axis regulating inorganic phosphate

Abstract: The solute carrier 34 (SLC34) family of membrane transporters is a major contributor to Pi homeostasis. Many factors are involved in regulating the SLC34 family. The roles of the bone mineral metabolism factors parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23) in Pi homeostasis are well studied. Intracellular Pi is thought to be involved in energy metabolism, such as ATP production. Under certain conditions of altered energy metabolism, plasma Pi concentrations are affected by the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…However, others suggest that posthepatectomy hypophosphatemia primarily relies on the action of phosphaturic factors. [37][38][39][40] In the literature, there are contrary reports on the effects of hypophosphatemia following major hepatectomy. 41 Although hypophosphatemia was associated with inferior outcomes after hepatectomy in some studies, 31,33,[42][43][44][45] other reports including ours demonstrated the superior outcome of postoperative hypophosphatemia along with poor outcome in the absence of postoperative hypophosphatemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others suggest that posthepatectomy hypophosphatemia primarily relies on the action of phosphaturic factors. [37][38][39][40] In the literature, there are contrary reports on the effects of hypophosphatemia following major hepatectomy. 41 Although hypophosphatemia was associated with inferior outcomes after hepatectomy in some studies, 31,33,[42][43][44][45] other reports including ours demonstrated the superior outcome of postoperative hypophosphatemia along with poor outcome in the absence of postoperative hypophosphatemia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, liver regeneration appears to be the dominant phosphate consumer for hepatectomy-related hypophosphatemia although the exact contribution of postoperative hyperphosphaturia remains unclear. However, others suggest that posthepatectomy hypophosphatemia primarily relies on the action of phosphaturic factors 37–40 …”
Section: Discussionmentioning
confidence: 99%
“…A common metabolite of both substances is NAD + which has been shown to directly (and maybe also indirectly) inhibit renal and intestinal Pi transport [46]. Very recent evidence suggests that NAD + mediates at least in part the circadian regulation of renal and intestinal Pi transporters [71,92]. On-going clinical trials test the efficacy of nicotinamide in combination with conventional phosphate binders in the NOPHOS (EU Clinical Trials Register 2013-000488-95) and COMBINE (ClinicalTrials.gov Identifier: NCT02258074) trials.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…In this regard, hormones such as insulin and glucagon regulate the tissue transfer of Pi, thereby affecting the blood Pi concentration. Furthermore, the circadian rhythm of the blood Pi concentration has been reported to be regulated by renal nicotinamide adenine dinucleotide metabolism, which is dependent on food intake [8][9][10]. Pi absorption/reabsorption and movement of Pi into and out of the cells are promoted by increasing or decreasing the expression levels of Pi transporters localized at cell membranes.…”
Section: Introductionmentioning
confidence: 99%